Planning and Budgeting Policy: Ensuring the Sustainability of Regional Development Implementation During Covid-19 and New Normal - Thadeus Fransesco Quelmo Patty; Ikhsan Budi Riharjo; Lilis Ardini (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study analyzed the implementation of refocusing policy and budget reallocation in the Sikka Sub-district in the budget year 2020. The study also examined the effect of the pandemic of COVID-19 on the planning and budgeting of the Sikka Government Budget 2021. Furthermore, the study was qualitative. The data were primary, in the form of interview results; which were directly taken from key informants or resources. In addition, the result showed that in 2020 the local government of Sikka had some changes in the documents of the Medium-term Development Plant from 2018 up to 2023. Meanwhile, there were 4 changes to the Local Budget through Bupati Sikka's rules until they were officially stated as local changes rules of the Local Budget. Therefore, the Government had to do Locally owned sources of Revenue adaptation and local budget rationalization. Those differences and changes were used to afford the events on Health, economic conditions, and the social safety net. Moreover, to spend their area development, the Government needed to have a local loan as part of the national economic recovery program.